Sphaeralcic Acid and Tomentin, Anti-inflammatory Compounds Produced in Cell Suspension Cultures of Sphaeralcea angustifolia - Pérez-Hernández, Juanita; González-Cortazar, Manasés; Marquina, Silvia; Herrera-Ruiz, Maribel; Meckes-Fischer, Mariana; Tortoriello, Jaime; Cruz-Sosa, Francisco; Nicasio-Torres, María del Pilar (Planta Medica, 2014)
Sphaeralcea angustifolia, an endangered plant species in Mexico, is employed to treat inflammatory processes and as a wound healing remedy. Scopoletin (1) was reported as one of the main bioactive compounds in this plant. Here, we isolated and identified compounds with anti-inflammatory properties from the suspension-cultured cells of S. angustifolia. The CH2Cl2 : CH3OH extract of the cells exhibited anti-inflammatory properties in acute inflammation models. Two compounds were isolated, 5-hydroxy-6,7-dimethoxycoumarin, named tomentin (2), and 2-(1,8-dihydroxy-4-isopropyl-6-methyl-7-methoxy)-naphthoic acid, denominated as sphaeralcic acid (3). Their structures were determined by spectroscopic and spectrometric analyses. The anti-inflammatory effects of both compounds were also evaluated. At a dose of 45 mg/kg, compound 2 inhibited the formation of λ-carrageenan footpad edema at 58 %, and compound 3 at 66 %. Local application of compound 2 (225 mM per ear) or 3 (174 mM per ear) inhibited the phorbol ester-induced auricular edema formation by 57 % or 86 %, respectively. The effect of compound 3 was dose-dependent and the ED50 was 93 mM.
Keywords: anti-inflammatory effects; suspension-cultured cells; coumarins; naphthoic acid derivate; Sphaeralcea angustifolia; Malvaceae; tomentin; sphaeralcic acid